2019
DOI: 10.1001/jamanetworkopen.2019.3667
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adult Congenital Heart Disease With Pregnancy, Maternal, and Neonatal Outcomes

Abstract: Key Points Question Do pregnancy, maternal, and neonatal outcomes differ in women with different types of adult congenital heart disease? Findings In this large cross-sectional study of 2114 women with adult congenital heart disease in Canada, maternal and neonatal outcomes varied by subtype of maternal heart condition. Adult congenital heart disease was associated with increased odds of adverse maternal, neonatal, and pregnancy outcomes during labor and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
53
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 44 publications
3
53
2
4
Order By: Relevance
“…Pregnant women with TOF were at high risk for maternal and neonatal complications as other types of heart disease, involving miscarriage, prematurity, premature rupture of membranes (PROM), preeclampsia, breech presentation, postpartum hemorrhage for the mothers; and small for gestational age, low birth weights, and cardiac anomalies for the newborns [4,18].Recently Ramage et al reported 2114 births to women with ACHD ( adult congenital heart disease) and suggested an association between several adverse neonatal and maternal outcomes and ACHD [19].They results showed that preterm births (<37 weeks gestation) were associated with 1.4 times higher odds among women with ACHD compared with those without ACHD.Women with ACHD also had higher odds of having a preterm birth at less than 32 weeks'gestation. Almost 12.8% of women with ACHD delivered an SGA infant compared with 8.7% of women without ACHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women with TOF were at high risk for maternal and neonatal complications as other types of heart disease, involving miscarriage, prematurity, premature rupture of membranes (PROM), preeclampsia, breech presentation, postpartum hemorrhage for the mothers; and small for gestational age, low birth weights, and cardiac anomalies for the newborns [4,18].Recently Ramage et al reported 2114 births to women with ACHD ( adult congenital heart disease) and suggested an association between several adverse neonatal and maternal outcomes and ACHD [19].They results showed that preterm births (<37 weeks gestation) were associated with 1.4 times higher odds among women with ACHD compared with those without ACHD.Women with ACHD also had higher odds of having a preterm birth at less than 32 weeks'gestation. Almost 12.8% of women with ACHD delivered an SGA infant compared with 8.7% of women without ACHD.…”
Section: Discussionmentioning
confidence: 99%
“…Although one case suffered with hypertension and cardiac failure, she was survived with professional care. Women at highest risk can benefit from preconception counseling and close clinical monitoring during pregnancy [19]. Careful interdisciplinary management among the cardiologist, obstetrician, anesthetist, and neonatologist, and detailed plans for delivery may have improved the prognosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently Ramage et al reported 2114 births to women with adult congenital heart disease (ACHD) and suggested an association between several adverse neonatal and maternal outcomes and ACHD [20]. They results showed that preterm births (<37 weeks gestation) were associated with 1.4 times higher odds among women with ACHD compared with those without ACHD.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, one patient with intrauterine fetal death undergone transvaginal complete curettage of uterine cavity, other uncorrected patients delivered by C-section successfully. Women at highest risk can benefit from preconception counseling and close clinical monitoring during pregnancy [20]. Careful interdisciplinary management among the cardiologist, obstetrician, anesthetist, and neonatologist, and detailed plans for delivery may have improved the prognosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently Ramage et al reported 2114 births to women with adult congenital heart disease (ACHD) and suggested an association between several adverse neonatal/maternal outcomes and ACHD [20].…”
Section: Discussionmentioning
confidence: 99%